Pengaturan Pelekatan Sidik Jari Dalam Minuta Akta Bagi Penyandang Tuna Daksa - Merry Rosari Kurniawati Weo; Dewi Cahyandari (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2023)
This study aims to understand and analyze related changes to the provisions in the Law on Notary Office and the urgency of Reconstructing the Legal Reconstruction of Attaching Fingerprints in Minutes of Deeds for Persons with Physical Disabilities. The research method used in this study is a normative legal research method with a statutory and conceptual approach. The results of this study explain that there have been several changes in the UUJN. The points that have changed in the latest UUJN are: the existence of a Special Substitute Notary; notary candidate apprentice; notary retirement age and its relation to the extension of retirement age; Notary authority in making deeds related to land; the authority of the Notary in making the minutes of the auction deed; Notary who is appointed as a State Official; and Implementation of notary position supervision. The urgency of the need for legal reconstruction is in order to achieve legal certainty from the implementation of the contents of Article 16 paragraph 1 letter (c). By reconstructing the contents of this article, the implementation can be carried out properly by a notary who is required to attach his fingerprints, especially for appearers at a notary who has physical limitations, namely the disabled. Studi ini bertujuan untuk untuk memahami dan menganalisis terkait perubahan pada ketentuan-ketentuan dalam Undang-Undang Jabatan Notaris serta urgensi Rekonstruksi Hukum Pelekatan Sidik Jari Dalam Minuta Akta Bagi Penyandang Tuna Daksa. Metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian hukum normatif dengan pendekatan perundang-undangan dan pendekatan konseptual. Hasil dari penelitian ini menjelaskan bahwa Terdapat beberapa perubahan dalam UUJN, Adapun point-point yang ada perubahan dalam UUJN terbaru yakni: keberadaan Notaris Pengganti Khusus; magang calon Notaris; usia pensiun Notaris dan kaitannya dengan perpanjangan usia pensiun; kewenangan Notaris dalam membuat akta yang berkaitan dengan pertanahan; kewenangan Notaris dalam membuat akta risalah lelang; Notaris yang diangkat menjadi Pejabat Negara; dan Pelaksanaan pengawasan jabatan Notaris. Urgensi diperlukannya rekonstruksi hukum ini adalah agar mencapai kepastian hukum dari pelaksanaan isi pasal 16 ayat 1 huruf ( c ). Dengan di rekonstruksi isi dari pasal ini maka dalam pelasanaannya dapat dijalankan dengan baik oleh notaris yang diwajibkan melekatkan sidik penghadap nya, khususnya bagi penghadap di notaris yang memiliki keterbatasan fisik yakni tuna daksa.